THE PHYSICOCHEMICAL CHARACTERIZATION AND KINETIC PARAMETER_x000D_ ASSESSMENT OF HYDROXYAPATITE CRYSTALS - POLAT, SEVGİ (My University, 2019)
The crystallization of hydroxyapatite (HAP) was analyzed in a batch system in pure medium and in the presence of butyricacid as an additive. The experiments were conducted at different additive concentrations and the influences of the additive wereinvestigated. Firstly, the crystals obtained were characterized by X-ray diffraction, Brunauer–Emmett–Teller, transmissionelectron microscopy, zeta potential measurement, Fourier transform infrared spectroscopy, and thermogravimetric analysis.The structure, surface areas, morphology, surface potential charges, functional groups and thermal decomposition behavior ofthe crystals were determined. In the next step, thermal decomposition kinetic profiles were modeled using the distributedactivation energy model (DAEM), Flynn-Wall-Ozawa (FWO) and Friedman models. All the models used provided accuratefits of the TGA data with acceptably high $R^2$ values. The value for the crystals obtained from the butyric acid containingmedium was about 589 kJ/mol higher than that found for the crystals from the pure medium (538 kJ/mol). According to theresults of the characterization and kinetic analysis, butyric acid could be employed as an additive for the production of HAPcrystals with the desired quality and physical properties.